Identification of a Cordyceps fumosorosea Fungus Isolate and Its Pathogenicity against Asian Citrus Psyllid, Diaphorina citri (Hemiptera: Liviidae) - Yaru Luo; Shujie Wu; Xinyu He; Desen Wang; Yurong He; Xiaoge Nian (Insects, 2022)
Diaphorina citri is the mainly transmitting vector of the citrus huanglongbing pathogen, which causes severe losses in in the citrus industry. In this study, we isolated a new entomopathogenic fungus, identified as member of Cordyceps fumosorosea based on morphology and ITS sequence analysis. We named C. fumosorosea SCAU-CFDC01 and evaluated its pathogenicity against D. citri nymphs and adults by immersion under laboratory and greenhouse conditions. Results showed that SCAU-CFDC01 was most pathogenic to young nymphs, followed by old nymphs and adults. The LC50 values of the fungus on nymphs and adults showed a declining trend over a 2–7-day period after inoculation. The LT50 (lethal time for a certain concentration to cause 50% mortality) values also presented a decreasing trend along with increasing conidia concentrations. For the results on greenhouse experiments, when 3rd and 5th instar nymphs were inoculated with 1 × 105 conidia mL−1, the survival rate of nymphs were lower, and the emergence rate of adults and female longevity was significantly reduced compared with the control. However, there were no significant effects on sex ratio of adults and male longevity. Our results showed SCAU-CFDC01 was highly pathogenic to D. citri, and may promote mycoparasite development for biological control of D. citri.